IMF Research Bulletin, March 2017. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2017)
This issue of the IMF Research Bulletin features recommended readings from IMF Publications and an update on recent IMF Working Papers and IMF Staff Discussion Notes. It also includes a special announcement welcoming Linda Tesar (University of Michigan) as the new editor of 'IMF Economic Review.' The Q and A section explores 'Seven Questions on China-Africa Relations' (Luiz Almeida, Wenjie Chen, and Oral Williams). The Research Summaries surveys 'Income Polarization in the United States' (Ali Alichi, Kory Kantenga, and Juan Sole); and 'The Future Wealth of Nations: World Trade in Services' (Prakash Loungani, Saurabh Mishra, Chris Papageorgiou, and Ke Wang).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet